Kajian Manajemen Lingkungan Terhadap Kejadian Malaria di Daerah Endemis, Kecamatan Kakuluk Mesak, Kabupaten Belu - Asa, Antonius Tae; Setiani, Onny; Raharjo, Mursid (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2005)
ABSTRACT Background : Malaria is still endemic disease in Indonesia, especially in Belu district. Many measures had been implemented to reduce malaria cases , but its rate is still quite high in any areas . The fluctuation of malaria cases were influenced by epidemiological and environmental factors. Prevention of malaria had been conducted simultaneously through clinical and environmental intervention. However, such intervention had no more impact, especially the environmental intervention. Such failure may be associated with the location of this area closed to the highest malaria rate (AMI) area in Belu District for four years later, namely : AMI 416/1000 population for year 2000, 527/1000 population for year 2001, 418/1000 population for year 2002, 468/1000 population for year 2003, and it rose tobe 493/1000 population for the year of 2004. Based on this fact, this study was conducted to study the environmental management related to the occurrence of malaria in endemic areas in working area of Atapupu Health Centre, Belu District. Furthermore, the study would also analyze the impact of vector and its larva. Method : This was a qualitative research using secondary data of the environmental management measure. The subject of this research was the malaria programmer and health worker who responsible for malaria program. They were the Head of Public Health Centre, laboratory technician, Co-assistant of entomologist. The program measures would be studied in this research focusing on planning of malaria program, the malaria control measure, collecting and reporting of data, and monitoring – evaluation. Result : Measures had been conducted for reducing malaria cases in Atapupu Health Center through fogging, mosquito netting by medical officials without involving related sector. Monitoring and evaluating have been conducted just through data collection and reporting the rate of cases which was found in Passive Case Detection activities, while monitoring and evaluation for the change of environmental condition that caused the growth of vector density had not been conducted yet. In implementing malaria program, the health center had not organized in integrated way yet, not so focus and systematic. Conclusion: Environmental management in malaria control program has not implemented well yet. So that malaria cases is still increase in the working area of Atapupu Health Center, Belu District. Key Words : Environmental management, malaria incidence, malaria program.